"Case study research: what, why and how?" - "Swanborn, Peter G." (New Delhi, 2010)
How should case studies be selected? Is case study methodology fundamentally different to that of other methods? What, in fact, is a case? Case Study Research: What, Why and How? is an authoritative and nuanced exploration of the many faces of case-based research methods. As well as the what, how and why, the author also examines the when and which - always with an eye on practical applications to the design, collection, analysis and presentation of the research. Case study methodology can prove a confusing and fragmented topic. In bringing diverse notions of case study research together in one volume and sensitising the reader to the many varying definitions and perceptions of 'case study', this book equips researchers at all levels with the knowledge to make an informed choice of research strategy.
Keywords: Case study methodology